IMPLEMENTASI PROGRAM LINK AND MATCH DENGAN DUNIA USAHA DAN DUNIA INDUSTRI PADA LULUSAN PEMASARAN SMK NEGERI 1 SURAKARTA - -, Septiana Dewi Cahyanti -; -, Mintasih Indriayu -; -, Sudarno - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
The objectives of this research are : 1) describe the implementation of link and match in business and industry field toward the graduate of marketing major at SMK Negeri 1 Surakarta; 2) describe the supporting factors and obstacles of the implementation of link and match in business and industry field toward the graduate of marketing major at SMK Negeri 1 Surakarta 3) describe the solution to overcome the problems. This research is a qualitative, case study research. Sources of data in this research are words, actions and written manuscripts. Techniques used to collect the subject of the research are purposive and snowball sampling. Techniques used to collect the data are observation, interview, documentation and triangulation. Technique used to test the data validity uses triangulation source technique. Technique used to analyze the data is interactive model which consist of data reduction, data display and verification. Based on the finding of the research, the implementation of the link and match program starts from preparation or planning stage, the implementation phase in the learning process in school and the cooperation toward industry, as well as the evaluation phase. Otherwise, the supporting factors of link and match program are: the cooperation between school and business and industry field and the positive feedback from students? parents and the government. In the other hand, the obstacles of the implementation of link and match divided in to two major factors; external and internal factors. The solutions to overcome the problem (a) to solve problem in internal factors: school should give provision to maximize the function of shop as practical laboratory, school will make cooperation with Luwes (b) to solve problem in external factors: school will try to maximize and customize the existing curriculum to the work processes in industry field so there is no deviation to basic competence which set by Education Department. Those five programs implemented to improved and support the graduate?s qualification to suit the needs and demands of business and industry world. Based on the findings, there is 52,5% of the marketing major graduate n 2017/2018 get the suitable jobs. There is 1,7% who opens the independent business with the suitable major criteria. Moreover, there is 45,8% of marketing major graduate who haven?t able to identified their jobs. The total number of 59 marketing graduate with waiting period to get the job is 5 months after the graduation time.